2013
DOI: 10.1159/000350401
|View full text |Cite
|
Sign up to set email alerts
|

Primary Headache and Silent Myocardial Ischemia in Patients with Coronary Artery Disease

Abstract: Objective: The mechanisms by which migraine is linked to ischemic vascular disease remain uncertain and are likely to be complex. The aim of this study was to investigate the correlation between silent myocardial ischemia (SMI) and a history of documented primary headache in a large population of patients with exercise-induced myocardial ischemia. Methods: The study involved 1,427 consecutive patients (918 symptomatic and 509 asymptomatic patients) with exercise-induced myocardial ischemia and documented coron… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 38 publications
(52 reference statements)
0
5
0
Order By: Relevance
“…The incidence of headache as a symptom of myocardial ischemia may be underestimated [1][2][3][4][5] . Culić et al [6] reported that headache is present (along with other symptoms) in 5.2% of patients with acute myocardial infarction.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The incidence of headache as a symptom of myocardial ischemia may be underestimated [1][2][3][4][5] . Culić et al [6] reported that headache is present (along with other symptoms) in 5.2% of patients with acute myocardial infarction.…”
Section: Discussionmentioning
confidence: 99%
“…Headache represents a rare symptom of myocardial ischemia [1][2][3][4][5] . We report a patient with ST-segment elevation acute myocardial infarction who presented to the emergency department complaining of headache without chest discomfort.…”
Section: Introductionmentioning
confidence: 99%
“…A recent work on a large CAD population by Falcone C et al, (2013) [10] suggests that the presence of primary headache could be a useful marker to identify subjects with susceptibility to pain and that its absence could be correlated with SMI. Data deriving by this study suggest that symptomatic patients with primary headache were more prone to pain.…”
Section: Ischemic Heart Diseasementioning
confidence: 99%
“…In multiple population-based studies was shown that patients with migraine are more likely to have chest pain symptoms [8][9][10]. Among which one large study in Australian patients showed a relationship between migraine and cardiovascular events and noted that subjects with migraine were twice as likely to have a self-reported history of myocardial infarction [11].…”
Section: Introductionmentioning
confidence: 99%
“…Atypical symptoms of myocardial infarction may delay the diagnosis, and therefore the proper management to rescue ischemic myocardium. Headache represents a rare symptom of myocardial ischemia [1][2][3][4][5] . We report a patient with ST-segment elevation acute myocardial infarction who presented to the emergency department complaining of headache without chest discomfort.…”
Section: Introductionmentioning
confidence: 99%